River blindness - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Dr Elizabeth Elhassan of the NGO Sight Savers International explains what her organisation is doing to alleviate the problem of river blindness among farming communities in Nigeria and other parts of west and central Africa